1996
DOI: 10.1021/jm950806n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Quantitative Structure−Activity Relationships of 17β-(Hydrazonomethyl)-5β-androstane-3β,14β-diol Derivatives That Bind to Na+,K+-ATPase Receptor

Abstract: A series of 17 beta-(hydrazonomethyl)-5 beta-androstane-3, beta,14 beta-diol derivatives was synthesized and evaluated in the displacement of [3H]ouabain binding from Na+,K(+)-ATPase. The data were explored with multiple linear regression and partial least-squares to find possible quantitatives structure-activity relationships. Good correlations were found between binding to the receptor and van der Waals volumes or molar refractivities of the 17 beta-hydrazonomethyl substituents and pKa values of the compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…From these new findings and the data reported in the previous papers, [3][4][5] we reasoned that this extraordinary activity could be ascribed to an interaction of the protonated amine substituent with a negatively charged site in the receptor. With the aim of finding if this putative "anionic site" really existed, we started a The EZ mixture is indicated where the amount of Z oxime is more than 10%.…”
Section: Introductionsupporting
confidence: 59%
“…From these new findings and the data reported in the previous papers, [3][4][5] we reasoned that this extraordinary activity could be ascribed to an interaction of the protonated amine substituent with a negatively charged site in the receptor. With the aim of finding if this putative "anionic site" really existed, we started a The EZ mixture is indicated where the amount of Z oxime is more than 10%.…”
Section: Introductionsupporting
confidence: 59%
“…6 A further shift of the iminic nitrogen atom is detrimental for the activity, as is demonstrated by compound 8, vinylogous derivative of compound 5, and is confirmed by the parallel low activity of the lactone 9, vinylogous derivative of digitoxigenin. The lower inhibitory potency of the syn isomer 6 versus its anti isomer 7 might be ascribed to the different steric arrangement preventing the proper orientation of the electron lone pair of the iminic nitrogen atom toward the hydrogen donor group of the enzyme and/or the ion-pair interaction.…”
Section: Discussionmentioning
confidence: 82%
“…6 The guanidinoamino compound 4 was obtained by catalytic hydrogenation of the corresponding hydrazono derivative 1 (Scheme 1). Compounds 5-7 and 8 were prepared from the aldehydes 14 and 15, respectively, and the appropriate hydrazino derivative in dioxane/water solution at pH 3 (Scheme 2); the two isomeric derivatives 6 and 7 were obtained in the same reaction and separated by flash chromatography.…”
Section: Chemistrymentioning
confidence: 99%
“…13 In naturally occurring digitalis glycosides the unsaturated g-and d-lactones present in 17b-position of the steroidal skeleton are associated with high affinity for the Na þ /K þ -ATPase receptor. 15,16 Recently, it was confirmed that basicity, i.e. a strong ionic interaction between one of carboxylate residues present in the a-subunit of the Na þ /K þ -ATPase and the cationic form of some digitalis like derivatives is relevant for interference with enzyme activity.…”
Section: Introductionmentioning
confidence: 99%